Perencanaan Strategis Sistem Informasi untuk Mendukung Integrasi Proses Bisnis pada PT Matra Digital Group - Revina Trisna Aini; Dafid Dafid (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
PT Matra Digital Group is a company operating in the digital and information technology sector, managing four business units: Dezainla (printing and apparel manufacturing), Mits (device repair services), Sewain (device rental), and Marco Digital Partner (digital marketing). This research was conducted to formulate a strategic information systems and information technology (IS/IT) plan capable of supporting data integration, real-time operational monitoring, and more effective management decision-making. The methodology implemented is the Ward and Peppard framework. This approach involved a profound evaluation of the external business environment (PEST and Porter's Five Forces), alongside an in-depth assessment of the organization's internal business environment (Value Chain) as well as its internal and macro IS/IT ecosystems. The study's findings indicate that the company's current information systems operate in isolation (siloed) across departments, thereby triggering data multi-interpretation and hindering operational alignment. Based on this evaluation, the outputs of this research formulate strategic recommendations for IS, IT, and IS/IT governance, as well as an application portfolio mapped via the McFarlan Strategic Grid. The primary implementation focus is directed toward an ERP-like Integrated Information System, a Business Intelligence Dashboard, and an Integrated Financial System, which are projected to accelerate the company's long-term digital governance.